Peroxide value and palm oil extraction yield from sterilised oil palm mesocarp / Siti Zulaikha Ruslan and Norashikin Ahmad Zamanhuri - Ruslan, Siti Zulaikha; Ahmad Zamanhuri, Norashikin (Universiti Teknologi MARA Shah Alam, 2023)
Conventional palm oil milling undergoes multiple processes including sterilisation and stripping process that introduce a significant amount of water, resulting in a large amount of wastewater. Sterilisation is the first step in milling, where it is the pre-treatment to deactivate enzymes that increase free fatty acid before oil extraction. Microwave heating softens the surface of the palm fruit mesocarp, making it much easier to extract by solvent extraction. To fill the gap of the previous study, which is to apply two processes of drying and extraction, Soxhlet extraction and microwave will be proposed as an alternative to extracting a higher yield of palm oil mesocarp, replacing the conventional method, which uses the screw pressing process. The power of microwave pretreatment was found to be the most significant factor contributing to poor oil quality. Hence, iodination titration will be used to study the peroxide value (PV) in the oil palm that was extracted. During the sterilisation process, the exposure time and weight of the fruit were constant at 6 minutes and 200 g, respectively. At 800 W of microwave power, without the presence of water, it demonstrated a higher yield, which is around 59.31 %. Peroxide values from sterilized oil palm mesocarp are less than 10 meq/kg; thus, using a microwave sterilisation process followed by the Soxhlet extraction method is an alternative technique to produce crude palm oil.